Pengaruh Sunset Policy terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan Perdesaan dan Perkotaan Kota Bandung - Idzni Widianti Agustin; Yeti Apriliawati; Arry Irawan (Indonesian Accounting Research Journal, 2021)
One of the problems in Land and Building Tax of Rural and Urban sectors (PBB-P2) is the low level of taxpayer compliance. Therefore, the Bandung Regional Revenue Management Agency makes efforts to improve taxpayers compliance, one of which is by implementing the Sunset Policy program. This study aims to determine the effect of Sunset Policy toward compliance of PBB-P2 taxpayers. The research method used is descriptive quantitative. The type of data used is self-report data and documentary data. The sample is determined based on the incidental method of 100 respondents. The data analysis used is simple linear regression. The results of this study are the Sunset Policy is in a good category, the compliance of PBB-P2 taxpayers is in the very good category, and the Sunset Policy has a positive and significant effect on the compliance of PBB-P2 taxpayers by 24,1%, while the remaining 75,9% is influenced by other variables.